The dynamic determinants of interest rates in Tanzania: A focus on inflation, money supply and exchange rates - Kikoti, Boniface (Mzumbe University, 2024)
A Dissertation Submitted in Partial/Fulfilment of the Requirements for Award of the Degree of Master of Science in Accounting and Finance (MSc A&F) of Mzumbe University.